Perlindungan Hukum terhadap Kreditor Preferen dalam Pemberesan Proses Kepailitan - Ali Murtadho, Nazhif (Indonesian Journal Publisher, 2024)
This research focuses on legal protection for preferred creditors in the bankruptcy process as stipulated by Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (UUKPKPU). The methodology employed is normative legal research with a statutory approach, specifically UUKPKPU. Data collection was conducted through literature studies and analyzed using descriptive, evaluative, argumentative, and prescriptive techniques. The research findings indicate that bankruptcy functions as a general seizure mechanism for debtor assets to protect creditor interests and ensure fair and proportional debt repayment. Creditors in bankruptcy are categorized into separatist, preferred, and concurrent creditors, with preferred creditors having priority privileges in debt repayment. The principle of creditorium parity and the pari passu prorata parte principle emphasize equality among creditors in obtaining repayment from the debtor's assets. Legal protection for preferred creditors aims to avoid conflicts among creditors and protect the interests of certain parties such as workers and the state. The conclusion is that bankruptcy confirms an equal position among creditors in obtaining receivables repayment from the debtor's assets, with preferred creditors enjoying special privileges regulated by law. The implementation of bankruptcy must be based on legal principles that ensure justice and balance in the distribution of debtor assets.